A review paper on Last Mile Logistics operation design, challenges and opportunities in Malaysia - Mun, Geet Ow Yong; Syriac, Nellikunnel Devasia (INTI International University, 2018)
This is a review paper on design, challenge and opportunity of Last Mile Logistics (LMP) operations in Malaysia. As business-to-customer online retail platform (ORP) industry becomes crowded in Malaysia, logistics emerges as prerequisite towards dominance of cyberspace. However, the widely adopted design of distribution model, namely the Hub and Spoke model, is sensitive towards demand spikes. Outsourcing has been identified as an opportunity to address such challenge. From the perspective of the ORP, outsourcing is a non-trivial alternative and if managed haphazardly it would sacrifice both customer service level as well as profitability. From the perspective of the outsourcing entities, namely the third party logistics service providers, emergence and expansion of players have been observed.